Frequency of Verbs in Lifestyle Column in The Jakart Post and The Relation to Text Characteristics: A Corpus-Based Analysis - Ikmi Nur Oktavianti; Zanuar Anggun Pramesti (Institut Agama Islam Negeri Palopo, 2019)
This study examines the use of verbs in Lifestyle column in The Jakarta Post to identify the frequency of verbs used in the column and to find out the relation between frequency of verbs and the characteristics of Lifestyle column as the staple product of soft news. This study collected the data, sentences containing lexical verbs, from Lifestyle articles labeled as Lifestyle Corpus comprising 29.195 words. The Lifestyle Corpus was loaded into Lancsbox corpus tool to get the assistance in identifying the use of the verbs. The data were analyzed both qualitatively (classifying the types of the verbs based on Scheibmann’s compilation and interpreting the relation between frequency and text characteristics) and quantitatively (counting the percentage of verb usage and list the verbs from the most frequent to the least frequent one). The results of the study show that the verb types most frequently used in Lifestyle of The Jakarta Post are material, verbal, and relational and the least frequent ones are possessive/relational, cognition, and perception/relational. The highest use of material verbs is plausible since the members of material verbs can also be used as phrasal verbs and used metaphorically. Following material, verbal verbs occupies the second most frequent verb of which it is in accordance with the nature of news text, that is to report something. Meanwhile, perception/relational verb indicates that the expression of subjective perception is less prominent in writing Lifestyle articles as it is also avoided in news writing in general. This strongly indicates that frequency of linguistic units is (1) affected by the nature of the linguistic units themselves or (2) affected by the characteristics of the text.